2016
DOI: 10.1155/2016/5912841
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Bilateral Permanent Subluxation of the Lateral Meniscus

Abstract: We report a case of bilateral, permanent subluxation of the lateral meniscus. To our knowledge, the present case is the first reported description of bilateral irreducible anterior dislocation of the posterior segment of the lateral meniscus. This disorder is characterized by a flipped meniscus sign of the lateral meniscus on sagittal magnetic resonance images of the knee joint, with no history of trauma or locking symptoms. A detailed examination of serial magnetic resonance images of the lateral meniscus can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The findings in our patient resemble a case of PSLM by Suganuma et al [ 9 ] in a 37-year-old female. They reported that she had no history of trauma or locking symptoms.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The findings in our patient resemble a case of PSLM by Suganuma et al [ 9 ] in a 37-year-old female. They reported that she had no history of trauma or locking symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…Her right knee which was more symptomatic had an osteochondral defect of 15 × 20 mm on the lateral femoral condyle. Suganuma et al [ 9 ] stated that PSLM appeared to be related to both congenital and environmental factors, as the dislocated meniscus needs to be adhered to the surrounding tissue. However, as evident in our case, there was no adhesion between the meniscus and the intercondylar space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations